EFEKTIFITAS BERMAIN HIALNG DALAM PASIR UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF PADA ANAK TUNAGRAHITA RINGAN - Sri - Febriani (Universitas Negeri Padang, 2013)
This research of background overshadow by Child of Intelegance Below which not yet recognized six letter (b, d, m, n, and q). Pursuant to this research the mentioned aim to prove effective of game lose in sand for defining letter. This research use type research of experiment with method of Single Subject Research (SRR) with A-B-A desain. Subjek Research is a Child of intelegance below of X Class 3/C. Assessment in this research of consistence and measure ability of child in mentioning, showing and writing down assessment and letter presented in the form of percentage. Result of this research indicate that, ability of Child of intelegance below of X in recognizing six letter mount, in the early the condition of baseline (A) which is done the seven of times rill of tes child only recognizing can mention two letter that is and b of d, at condition of conducted intervention counted ten times tes ability of child mount with approach use game lose in sand that is child can mention, showing and lettering. And last is activity of baseline (A2), this activity is done by the five of times rill of tes, after activity of intervention discontinued, in the reality ability of child can maintain its ability in mentioning, showing and lettering. Data collected by doing tes how many child can show, mentioning and writing down letter truly. Thereby proven by told hypothesis that game lose in effective sand in improving ability recognize six letter at Child of intelegance below of class X 3/C in SLB Fan Redha Field. Relate to result of research in recognizing letter at Child of intelegence below of X mount, hence researcher suggest to teacher to use game lose in sand in improving ability recognize letter for study hereinafter.